Strategy to Increase Sales Through Packaging Labels and Banner on Mushroom UMKM “MBAH MI” - Brata, Nugroho Trisnu; Triyaka, Triyaka; Saiya, Susana Fadhara; Pratiwi, Megawati Vika; Prayogo, Bagas; Ratri, Indraswari Kumolo; Afrida, Lutfiana; Anggiarini, Sukma; Zayyaan, Ghinna Al; Saputra, Gandung Surya; Afrijal, Muhamad Afif; Wulandari, Siti Nur; Dzaky, Ammar Fuad (Universitas Negeri Semarang, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a central role in the national economy, influencing economic growth and being the main driver of national development. The general definition of MSMEs includes three categories of businesses with specific assets and turnover that play an important role in Indonesia's economic development. In the snack food sector, MSMEs such as Mbah Mi Krispi Mushrooms, which focus on the production of crispy mushrooms, are a clear example. However, observations of this business showed a lack of packaging labels without contact information for the business owner and the absence of promotional media such as banners. This condition limits sales potential. Therefore, this activity aims to redesign packaging labels with additional contact information and design banners as promotional media. This step is expected to increase the selling power of products and raise the profile of MSMEs so that they are better known to the wider public.